Signal peptide–independent secretion of keratin-19 by pancreatic cancer cells - Philip Moresco; Jonathan P. Kastan; Jung-in Yang; Rishvanth Prabakar; Z. Larkin Kelley; Francesca Minicozzi; Dexter W. Adams; Paolo Cifani; David A. Tuveson; Douglas T. Fearon (Proceedings of the National Academy of Sciences, 2025)
The exclusion of T cells causes immune escape of pancreatic ductal adenocarcinoma (PDA). T cell exclusion is mediated by the interaction between CXCR4 on T cells and its ligand, CXCL12, which is complexed to keratin-19 (KRT19) on the surface of PDA cells. KRT19 secretion by PDA cells is essential to this process but is unusual because KRT19 lacks an endoplasmic reticulum (ER)-directing signal peptide (SP). By using biotinylation by an ER-restricted TurboID system and a split-GFP assay in PDA cells, we demonstrate that KRT19 enters the ER via its “head” domain. Additionally, KRT19 is shown to interact with the signal recognition particle and its secretion is sensitive to canonical protein secretion inhibitors. In vivo, mouse tumors formed with ER-TurboID-expressing PDA cells contain biotinylated KRT19. In contrast, keratin-8 (KRT8), which colocalizes with KRT19 on the surface of PDA cells, does not enter the ER. Rather, KRT8 is externalized via secretory autophagy possibly in a complex with KRT19. Thus, despite lacking a classical SP, PDA cells secrete KRT19 to capture CXCL12 and protect against immune attack.